Social Policies, Conditional Cash Transfer Programs and Types of Indebtedness: Possible Articulations in Twenty First Century Argentina - Dettano, Andrea (2019)
This article aims at presenting some of the relations and implications of consumption, indebtedness, financialization, and social policies from a sociological perspective. To achieve this, turn to some of our own research, carried on since 2016, on different types of loans granted to Conditional Cash Transfer Programs (CCTs) beneficiaries by private banks which manage the payment of these loans. Within this framework, this article aims at describing the types of loans available for the Asignación Universal por Hijo para Protección Social (Universal Allowance per Child for Social Protection) beneficiaries in Argentina, including both those offered by private banks and by the government institutions which manage the payments. This is an exploratory-qualitative study of the available biographical information on the access and management of loans to Universal Allowance per Child beneficiaries. The argumentation strategy will be as follows: First, we reclaim conceptualizations about social policies; then, second, we describe the modalities of these conceptualizations, such as the CCTs; third, we trace consumption and indebtedness as central aspects of social structures; fourthly, we analyze the modalities of indebtedness available to the Universal Allowance per Child beneficiaries; and we close with thoughts about the emphasis on the mode in which subjects are consolidated, form state actions, as consumers and indebted subjects.